Application of Physical Exercise in Non-Hemorrhagic Stroke Patients with Physical Mobility Impairment at Gunung Jati Hospital, Cirebon City - Iyep Maulana, Ahmad; Wahyuni Romadhon, Lily; Setyo Dwi Andhini, Citra (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Stroke is damage to the brain that occurs due to a sudden decrease or interruption in the flow of oxygen in the blood. The objective of this study is to provide appropriate nursing care for patients with non-hemorrhagic stroke in a detailed and comprehensive manner, with a focus on the application of physical exercise for patients with non-hemorrhagic stroke and physical mobility impairments at RSD Gunung Jati Hospital in Cirebon City. Method: This study adopts a descriptive design using a case study approach. The steps include data collection, diagnosis, planning, intervention, and evaluation. The study was conducted at RSD Gunung Jati Hospital in Cirebon City in February 2025, with data collected through interviews, observations, physical examinations, and medical records. Result: After undergoing Range of Motion (ROM) training, patients showed improvements in flexibility, muscle strength, and movement coordination. Conclusion: These findings indicate that an approach using joint strengthening exercise techniques contributes to reducing physical mobility issues and enhancing patients' independence in performing daily activities.